PEMBERIAN EDUKASI MELALUI WEBINAR PENERAPAN SELF-FORGIVENESS UNTUK MENINGKATKAN KESEJAHTERAAN PSIKOLOGIS - Dandy Maulana Akbar; Ulfa Irza Labiba Zubaidah; Aliyya Welbi Noveli; Amanina Zulfati Fakhira; Natasya Putri Namira; Annisa Anin Sari; Ahmad Rusdi (Universitas Jenderal Soedirman, 2021)
This study aims to increase awareness regarding the importance of psychological well-being through the application of self-forgiveness. The method of measuring self-forgiveness for webinar participants is done by providing a pre-test and post-test. The scale used in this study is one of the aspects of the ‘Heartland Forgiveness Scale’, which is ‘forgiveness of self’ by Laura Yamhure Thompson, Snyder, C.R., Lessa Hoffman. Participants in this study were 121 participants, both male and female, aged 19 until 33 years, who were looking for their identity, and trying to learn to forgive themselves. Analysis of the data in this study using Paired Sample T-Test. The results showed that the pre-test mean score was 16.70 and the post-test mean score was 18.36, which can be said significant with the value p=0.000 (p<0.05). Based on the correlation test, the value was obtained p=0.394 (p>0.05) which indicated there was no correlation between the pre-test and post-test of participants in the webinar. So it can be concluded that providing education through webinars can improve participants' understanding regarding the application of self-forgiveness to improve psychological well-being.